Politics and rhetoric in the Corinthian epistles - Welborn, L.L. 1953- (Macon, GA Mercer University, 1997)
Includes bibliographical references and indexes.
Keywords: Bible. N.T. Corinthians -- language, style; Rhetoric in the Bible